The metaphor of the bees in Columella: war and diplomacy under Nero - Carvalho, Helton Lourenço (Romanitas - Revista de Estudos Grecolatinos, 2021)
Beekeeping in ancient societies, in addition to composing the economic and productive framework, also integrated the literary repertoire that through an allegorical-metaphorical language reflected on power relations and government models that a portion of the literate aristocracy postulated as being the ideal one. In this sense, the objective of this article will be to understand part of the prescriptions of the ninth book of De Re Rustica as being a metaphor that reflects on the tensions involving the Emperor, Senate and the Army, especially with regard to the conflicts on the eastern border during the Nero’s Principate.